New pentasubstituted pyrrole hybrid atorvastatin–quinoline derivatives with antiplasmodial activity. Issue 8 (15th April 2016) - Carvalho, Rita C.C.; Martins, Wagner A.; Silva, Tayara P.; Kaiser, Carlos R.; Bastos, Mônica M.; Pinheiro, Luiz C.S.; Krettli, Antoniana U.; Boechat, Núbia
Graphical abstract: Abstract: Cerebral malaria is caused by Plasmodium falciparum . Atorvastatin (AVA) is a pentasubstituted pyrrole, which has been tested as an adjuvant in the treatment of cerebral malaria. Herein, a new class of hybrids of AVA and aminoquinolines (primaquine and chloroquine derivatives) has been synthesized. The quinolinic moiety was connected to the pentasubstituted pyrrole from AVA by a linker group (CH2 ) n = 2–4 units. The activity of the compounds increased with the size of the carbons chain. Compound with n = 4 and 7-chloroquinolinyl has displayed better activity (IC50 = 0.40 μM) than chloroquine. The primaquine derivative showed IC50 = 1.41 μM, being less toxic and more active than primaquine.